Simple Proofs of Two Dirac-type Theorems Involving Connectivity - Mosesyan, Carlen M.; Nikoghosyan, Mher Zh.; Nikoghosyan, Zhora G. (Mathematical Problems of Computer Science, 2021)
In 1981, the third author proved that each 2-connected graph G with δ ≥ (n+k)/3 is hamiltonian and each 3-connected graph contains a cycle of length at least min n, 3δ-k, where n denotes the order, δ - the minimum degree and k- the connectivity of G. Short proofs of these two results were given by Häggkvist and Yamashita, respectively, occupying more than three pages for actual proofs altogether. Here we give much simpler and shorter proofs actually occupying the two-thirds of a page.